Tumor-Associated Macrophages: Critical Players in Drug Resistance of Breast Cancer - Xiao, Maoyu; He, Jun; Yin, Liyang; Chen, Xiguan; Zu, Xuyu; Shen, Yingying (Frontiers in Immunology, 2021)
Drug resistance is one of the most critical challenges in breast cancer (BC) treatment. The occurrence and development of drug resistance is closely related to the tumor immune microenvironment (TIME). Tumor-associated macrophages (TAMs), the most important immune cells in TIME, are essential for the drug resistance in BC treatment. In this article, we summarize the effects of TAMs on the resistance of various drugs in endocrine therapy, chemotherapy, targeted therapy, and immunotherapy, and their underlying mechanisms. Based on the current overview of the key role of TAMs in drug resistance, we discuss the potential possibility for targeting TAMs to reduce drug resistance in BC treatment, and the prospects for clinical applications.